The Influence of Social Media Marketing, Influencer Endorsement, and Content Personalization on Buying Intention among Generation Z Consumers in Indonesia - Saleh, Mohamad Zein; Iskandar, Yusuf (Indonesian Research Journal on Education, 2025)
This study analyzes the influence of social media marketing, influencer endorsement, and content customization on purchasing intention among Generation Z consumers in Indonesia. Based on a quantitative approach with 150 respondents, the study applies a Likert scale (1-5) and data analysis using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results indicate that all three variables significantly impact buying intention, with influencer endorsement impacting most, followed by content personalization and social media marketing. The model explains 65% of the variance in buying intention, indicating its high explanatory power. This research adds to our understanding of the marketing strategies that effectively influence Generation Z's purchasing habits and offers real-world implications for business organizations seeking to maximize their internet marketing campaigns.